2007
DOI: 10.1159/000105141
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Ghrelin/Growth Hormone Secretagogue Receptors

Abstract: Ghrelin is a gastric polypeptide displaying strong GH-releasing activity by activation of the type 1a GH secretagogue receptor (GHS-R1a) located in the hypothalamus-pituitary axis. GHS-R1a is a G-protein-coupled receptor that, upon the binding of ghrelin or synthetic peptidyl and non-peptidyl ghrelin-mimetic agents known as GHS, preferentially couples to Gq, ultimately leading to increased intracellular calcium content. Beside the potent GH-releasing action, ghrelin and GHS influence food intake, gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 460 publications
2
39
0
1
Order By: Relevance
“…Furthermore, in human pancreatic islets, GHS-R1a immunoreactivity partially overlaps with insulin-positive b-cells, as demonstrated by double immunofluorescence staining for both GHS-R1a and insulin (Granata et al 2007), indicating that human b-cells might also be responsive to ghrelin stimulation. Like the two forms of ghrelin, GHS-R1a expression was shown in human and rat developing pancreatic islets, from early gestation to adult (Date et al 2002, Chanoine & Wong 2004, Granata et al 2007, Ueberberg et al 2009). …”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 90%
See 3 more Smart Citations
“…Furthermore, in human pancreatic islets, GHS-R1a immunoreactivity partially overlaps with insulin-positive b-cells, as demonstrated by double immunofluorescence staining for both GHS-R1a and insulin (Granata et al 2007), indicating that human b-cells might also be responsive to ghrelin stimulation. Like the two forms of ghrelin, GHS-R1a expression was shown in human and rat developing pancreatic islets, from early gestation to adult (Date et al 2002, Chanoine & Wong 2004, Granata et al 2007, Ueberberg et al 2009). …”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 90%
“…Only one study reported b-cell restricted ghrelin expression in the human pancreas (Volante et al 2002). Ghrelin expression in insulin-producing cells was, however, also demonstrated in rodent-derived b-cell lines (Granata et al 2007). Interestingly, AG and UAG were found expressed both in the adult and perinatal rat pancreas (Date et al 2002, Chanoine et al 2006, suggesting autocrine/paracrine effects throughout the organ's development.…”
Section: Ag Uag and Ob Expression In The Endocrine Pancreasmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon binding to the GHS receptor, which has been renamed ghrelin receptor (GRLN-R1a; Davenport et al 2005), GHSs activate pathways that regulate the activation of downstream MAPK, protein kinase B (PKB/Akt), nitric oxide synthase and adenosine monophosphate-activated protein kinase cascades in different cellular systems (Petersenn 2002). GRLN-R1a activation leads to an increase in intracellular levels of Ca 2C via phosphatidylinositol-specific phospholipase C (Camiña et al 2003, Muccioli et al 2007). Ghrelin and GHRP-6 stimulate proliferation of different cell types (Dieguez & Casanueva 2000, Pettersson et al 2002, Thompson et al 2004, Rossi et al 2009) and may also affect the CNS by protecting neurons from apoptosis (Frago et al 2002, 2011, Delgado-Rubin de Célix et al 2006, Delgado-Rubin et al 2009).…”
Section: Introductionmentioning
confidence: 99%